Islamic Marketing Mix: The Strategy on Local Indonesian Halal Products - Rekno Juminten; Ahmad Lukman Nugraha (Value Management Research, 2024)
This study aims to find out how the marketing strategy applied by CV Yumeda Pangan Sejahtera which is one of the local products from Indonesia in the face of competition in halal food market. This study uses a qualitative and case study with data collection methods by interview, observation and documentation and data analysis using pattern matching and explanation building analysis techniques. The results of the study found that CV Yumeda Pangan Sejahtera in its marketing followed the principles of the Islamic marketing mix such as: 1) the products offered have halal and tayyib quality. 2) The Price Strategy uses Cost of Goods Sold (HPP) and adjusts to the benefits and competitiveness of prices with other products. 3) The Promotional Strategies that have been implemented are very well guarded from some forbidden things, that seen from postings on social media, nothing forbidden is found. And participate in several events that have been facilitated by the Ministry and other events. 4) The distribution strategy that has been implemented is very effective to avoid losses between the two parties and the flow of distributing products to consumers more quickly hammering various services both offline and online.